Phytophthora infestans population structure: a worldwide scale (2012)
Phytophthora infestans, the causal agent of late blight disease in potato and other members of the Solanaceae family, is responsible for causing the Irish potato famine and, even today, it causes enormous economic losses all over the world. For the establishment of an adequate pest management strategy, the determination of population structure is required. To characterize P. infestans populations worldwide two allozymes, Gpi (Glucose-6-phospate isomerase) and Pep (Peptidase), the RG57 DNA RFLP fingerprinting probe, as well as resistance to the fungicide metalaxyl and the mating type, have been used as markers. P. infestans populations in Mexico have been one of the main focuses of research in the population biology of this pathogen because this country has been considered as one of the possible centers of origin of this oomycete. In this review we present the population structure of P. infestans in Mexico, Europe, Africa, Asia, North America, and South America expanding on the present situation of P. infestans in Colombia. Finally, we will discuss different lines of research that are being carried out today with respect to P. infestans in Colombia, which have shown the importance of continuing the study of this devastating plant pathogen in our country.